Mutation screening of ASMT, the last enzyme of the melatonin pathway, in a large sample of patients with Intellectual Disability - Tzschach Andreas; Launay Jean-Marie; Delorme Richard; Van Esch Hilde; de Brouwer Arjan; Moreno Sarah; Jamain Stéphane; Dumaine Anne; Poirier Karine; Botros Hany; Pagan Cecile; Kalscheuer Vera; et al. (BMC, 2011)
Abstract Background Intellectual disability (ID) is frequently associated with sleep disorders. Treatment with melatonin demonstrated efficacy, suggesting that, at least in a subgroup of patients, the endogenous melatonin level may not be sufficient to adequately set the sleep-wake cycles. Mutations in ASMT gene, coding the last enzyme of the melatonin pathway have been reported as a risk factor for autism spectrum disorders (ASD), which are often comorbid with ID. Thus the aim of the study was to ascertain the genetic variability of ASMT in a large cohort of patients with ID and controls. Methods Here, we sequenced all exons of ASMT in a sample of 361 patients with ID and 440 controls. We then measured the ASMT activity in B lymphoblastoid cell lines (BLCL) of patients with ID carrying an ASMT variant and compared it to controls. Results We could identify eleven variations modifying the protein sequence of ASMT (ID only: N13H, N17K, V171M, E288D; controls only: E61Q, D210G, K219R, P243L, C273S, R291Q; ID and controls: L298F) and two deleterious splice site mutations (IVS5+2T>C and IVS7+1G>T) only observed in patients with ID. We then ascertained ASMT activity in B lymphoblastoid cell lines from patients carrying the mutations and showed significantly lower enzyme activity in patients carrying mutations compared to controls (p = 0.004). Conclusions We could identify patients with deleterious ASMT mutations as well as decreased ASMT activity. However, this study does not support ASMT as a causative gene for ID since we observed no significant enrichment in the frequency of ASMT variants in ID compared to controls. Nevertheless, given the impact of sleep difficulties in patients with ID, melatonin supplementation might be of great benefit for a subgroup of patients with low melatonin synthesis.